2008
DOI: 10.3892/or.20.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive immunotherapy for pancreatic cancer: Cytotoxic T lymphocytes stimulated by the MUC1-expressing human pancreatic cancer cell line YPK-1

Abstract: MUC1 is a tumor-associated antigen that is overexpressed in invasive ductal carcinomas of the pancreas (PC). MUC1-specific cytotoxic T lymphocytes (CTLs) recognize MUC1 molecules in a HLA-unrestricted manner. In this study, we performed adoptive immunotherapy (AIT) in patients with PC with CTLs stimulated by the MUC1expressing human PC cell line YPK-1. To induce CTLs, peripheral blood mononuclear cells (PBMCs) were cultured for 3 days with inactivated YPK-1 cells and then stimulated with interleukin (IL)-2 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 33 publications
2
43
1
Order By: Relevance
“…We recently decided to investigate MUC1 expression in colorectal cancer because it is a marker for poor prognosis 4 , its expression may affect the selection of chemotherapeutic agents and use of MUC1-cytotoxic T-lymphocyte CTL immunotherapy 5 , and little is reported about MUC1 expression in colorectal cancer tissues to date 6 7 .…”
Section: Introductionmentioning
confidence: 99%
“…We recently decided to investigate MUC1 expression in colorectal cancer because it is a marker for poor prognosis 4 , its expression may affect the selection of chemotherapeutic agents and use of MUC1-cytotoxic T-lymphocyte CTL immunotherapy 5 , and little is reported about MUC1 expression in colorectal cancer tissues to date 6 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although MUC1-specific antibodies and/or CTLs were detected in host and protected the host from attacking by tumor cells that express MUC1 (Johnen et al 2001), they were not adequate to generate effective anti-tumor immunity to totally inhibit the growth of tumor (Brossart et al 2000;Snyder et al 2006). Moreover, clinical trials with MUC1 showed that MUC1 is a relatively poor immunogen in human beings (Kawaoka et al 2008;Sugiura et al 2008) and that the induction of clinically effective anti-tumor immune responses had not been achieved. Consequently, it is necessary to develop new vaccination protocols to induce strong anti-tumor immune responses that are applicable for the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 95%
“…Treatment strategies targeting at the residual cancer cells, which are responsible for local recurrence and metastasis, are therefore necessary. Immunotherapy is expected to improve the prognosis of pancreatic cancer because it can act specifically against the tumor (Kawaoka et al 2008). Adoptive immunotherapy for pancreatic cancer has included the use of peptide vaccine, dendritic cell (DC) vaccine and DNA vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than being isolated from the tumor, lymphocytes are obtained from the peripheral blood, after which they are exposed to retroviral vectors encoding for specific genetically modified TCR designed to target specific tumor antigens. In the PDAC setting, Muc1-specific autologous T cells isolated from patients'PBMCs were expanded by incubation with a Muc1-presenting cell line prior to administration to eight patients with unresectable and 20 patients with resectable PDAC postsurgically [193]. This treatment reduced postsurgical hepatic recurrence and improve survival with respect to surgery alone, although the overall benefit was minimal (median survival: 17.8 vs. 14.0 months).…”
Section: Adoptive T Cell Immunotherapymentioning
confidence: 99%